2008
DOI: 10.1128/mcb.01861-07
|View full text |Cite
|
Sign up to set email alerts
|

The Histone-Like NF-Y Is a Bifunctional Transcription Factor

Abstract: Promoters and enhancers that activate RNA polymerase II (Pol II)-transcribed mRNA genes are formed by a combinatorial puzzle of short sequences recognized by sequence-specific regulators. Among such elements, the CCAAT box is known to be one of the most frequent. This has been illustrated by several unbiased bioinformatic studies of large sets of vertebrate promoters (16,19,21,29,35,48,57). Testing has shown that the CCAAT box significantly contributes to promoter activity (34).Different entities contain the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 60 publications
6
85
0
3
Order By: Relevance
“…NFY was shown to bind directly and constitutively to the ER stress-response element sequences in promoters of the induced genes (46,54) and was also reported to interact with GCN5 (13). A dominant negative version of NF-YA was reported to lead to defects in the transcription of genes normally associated with H3K4me3 and H3K9-14ac active marks in HeLa cells (11). Thus, all these data together with our results show that both NFY and SAGA are indispensable for normal stimulation of ER stress-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…NFY was shown to bind directly and constitutively to the ER stress-response element sequences in promoters of the induced genes (46,54) and was also reported to interact with GCN5 (13). A dominant negative version of NF-YA was reported to lead to defects in the transcription of genes normally associated with H3K4me3 and H3K9-14ac active marks in HeLa cells (11). Thus, all these data together with our results show that both NFY and SAGA are indispensable for normal stimulation of ER stress-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) The use of dominant-negative NF-YA vectors 54 and, more recently, the inactivation of NF-Y subunits by small interfering RNA (siRNA) or short hairpin RNA (shRNA) interference allowed the in vivo confirmation that a CCAAT promoter is regulated by NF-Y (reviewed in Dolfini et al 55 ). (v) Genomic analysis by ChIP-on-Chip [56][57][58][59] and ChIP-Seq 60 confirmed that NF-Y binds to Y/CCAAT in vivo. These experiments further refined the NF-Y PSFM ( Figure 2).…”
Section: Y and Ccaat: Two Names One Entitymentioning
confidence: 99%
“…35,36 In correlative ChIP on chip studies, NF-Y overlaps significantly with H3K4me3 and H3K9-14ac, and genes enriched for NF-Y and histone PTMs are associated with expression. 37 Importantly, the impact of NF-Y removal was dramatic on important methylation marks (H3K4me3, H3K79me2 and H3K36me3), suggesting that NF-Y is at the heart of the regulation of histone PTMs in core promoters. [38][39][40] It is unknown, however, whether NF-Y has a role in the deposition and regulation of histone acetylation.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, transcription of CCAAT genes are dramatically reduced by the NF-YA DN. [37][38][39][40] We examined G 2 /M cells blocked by Nocodazole treatment (the experimental set-up was described earlier and the efficiency of the NF-YA DN in affecting NF-Y-dependent transcription was monitored by qRT-PCR). 40 We performed ChIP assays with the specific antibodies (Fig.…”
Section: Role Of Nf-y In the Establishment Of The Acetylation Landscapementioning
confidence: 99%